2017
DOI: 10.3390/bioengineering4010015
|View full text |Cite
|
Sign up to set email alerts
|

Composite Biomaterials Based on Sol-Gel Mesoporous Silicate Glasses: A Review

Abstract: Bioactive glasses are able to bond to bone and stimulate the growth of new tissue while dissolving over time, which makes them ideal materials for regenerative medicine. The advent of mesoporous glasses, which are typically synthesized via sol-gel routes, allowed researchers to develop a broad and versatile class of novel biomaterials that combine superior bone regenerative potential (compared to traditional melt-derived glasses) with the ability of incorporating drugs and various biomolecules for targeted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…Mesoporous BGs (MBGs), which have been widely experimented as carriers for therapeutic ions and biomolecules and exhibit a controlled delivery capability for such agents [ 98 ], could partly overcome this problem by being embedded as high-added-value inclusions in biodegradable polymers. Many studies have been reported on the fabrication of MBG/polymer composites in the field of bone tissue engineering [ 99 ], but, to date, none of these constructs has been proposed for cardiac or lung tissue engineering. In general, applications in soft tissue engineering are dramatically scarce; only Jia et al [ 100 ] suggested the use of MBG/chitosan composite films to induce hemostasis and accelerate wound healing.…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Mesoporous BGs (MBGs), which have been widely experimented as carriers for therapeutic ions and biomolecules and exhibit a controlled delivery capability for such agents [ 98 ], could partly overcome this problem by being embedded as high-added-value inclusions in biodegradable polymers. Many studies have been reported on the fabrication of MBG/polymer composites in the field of bone tissue engineering [ 99 ], but, to date, none of these constructs has been proposed for cardiac or lung tissue engineering. In general, applications in soft tissue engineering are dramatically scarce; only Jia et al [ 100 ] suggested the use of MBG/chitosan composite films to induce hemostasis and accelerate wound healing.…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Natural tissues exhibit the unique ability of self-healing and repair, which synthetic implants do not have. A special class of recently-developed biomaterials, the so-called “hybrids”, are perhaps the very last frontier for obtaining implants with tissue-like properties [ 80 ]. Hybrid sol-gel materials are composed of interpenetrating networks of inorganic and organic phases, which are able to intimately interact at the nanoscale, thus allowing the whole material to behave as a single phase, unlike “conventional” nanocomposites [ 81 ].…”
Section: Grand Challenges For the Future—where Are We Going?mentioning
confidence: 99%
“…The interested reader is addressed to a recent review dealing with composite systems and biomedical cements including bioactive phases …”
Section: Other Forms Of Applications: Coatings Fibres and Compositesmentioning
confidence: 99%